2004
DOI: 10.1002/ijc.20356
|View full text |Cite
|
Sign up to set email alerts
|

Dietary agent indole‐3‐carbinol protects female rats against the hepatotoxicity of the antitumor drug ET‐743 (trabectidin) without compromising efficacy in a rat mammary carcinoma

Abstract: ET-743, an experimental antitumor drug with promising activity in sarcoma, breast and ovarian carcinoma, is currently under phase 2 clinical evaluation. It is hepatotoxic in animals and patients. We tested the hypothesis that indole-3-carbinol (I3C), the hydrolysis product of glucosinolates occurring in cruciferous vegetables, may protect against ET-743-induced hepatotoxicity in the female Wistar rat, the animal species with the highest sensitivity toward the adverse hepatic effect of this drug. Hepatotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…[106][107][108][109][110] Shertzer's group found that I3C protects mice from N-nitrosodimethylamine-mediated liver damage. 107 Treatment with 50 mg/kg body weight of I3C by gavage, 1 hr prior to NDMA, substantially protected against hemorrhagic lesions.…”
Section: I3c Exhibits Hepatoprotective Activity From Carcinogensmentioning
confidence: 99%
See 1 more Smart Citation
“…[106][107][108][109][110] Shertzer's group found that I3C protects mice from N-nitrosodimethylamine-mediated liver damage. 107 Treatment with 50 mg/kg body weight of I3C by gavage, 1 hr prior to NDMA, substantially protected against hemorrhagic lesions.…”
Section: I3c Exhibits Hepatoprotective Activity From Carcinogensmentioning
confidence: 99%
“…108 Tanaka's laboratory showed the inhibitory effect of I3C on diethylnitrosamine-induced hepatocarcinogenesis in male ACI/N rats and Donald's group found that I3C protects female rats against the hepatotoxicity of the antitumor drug ET-743 (trabectidin) without compromising efficacy in a rat mammary carcinoma. 106 Goeger's group found that I3C inhibits aflatoxin B1 (AFB1) carcinogenesis through the modulation of the distribution and metabolism of AFB1 109 and Shukla's laboratory showed protective effects of I3C on cyclophosphamide-(CP) induced clastogenecity in mouse bone marrow cells. 110 The results revealed a significant inhibition in the frequencies of CP-induced CAs and aberrant cells in bone marrow cells of I3C-supplemented Swiss albino mice.…”
Section: I3c Exhibits Hepatoprotective Activity From Carcinogensmentioning
confidence: 99%
“…In recent years, a few studies have hinted at the potential for I3C to enhance chemotherapeutic regimes [12,29,30]. Yet to date, combinatorial options remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…I3C is currently in clinical trial for treatment of recurrent respiratory papillomatosis [5,6] and cervical intraepithelial neoplasia [7,8] and has been shown to be well tolerated at doses up to 400mg/day [9]. Pharmacokinetic studies of I3C disposition have revealed systemic doses of up to 170μmol/L in tissue [10], which equates with in vitro efficacy particularly in the liver [11,12] which along with lymph nodes [13,14], is the major site for colorectal metastasis. I3C has been shown to exhibit both anti-proliferative and anti-invasive potential [15] via a variety of mechanisms, including up-regulation of E-cadherin and β-catenin at the cytoplasmic membrane [16,17], concurrent with down-regulation of nuclear β-catenin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Индол-3-карбинол защищал крыс от токсического действия трабектедина при сохранении его терапевтического действия при РМЖ. Существенно, что защитный эффект индол-3-карбинола не сопровождался сни-жением содержания трабектедина в печени, что ука-зывает на наличие альтернативных путей его деток-сикации [53].…”
unclassified